KAJIAN PERBANDINGAN DESAIN PERENCANAAN DAN PELAKSANAAN PEKERJAAN TIMBUNAN BENDUNGAN TIU SUNTUK, KAB. SUMBAWA BARAT - Alexander Christian Tibarrena; Wikan Kresno Sadono (Racic : Rab Construction Research, 2025)
During the construction of Tiu Suntuk Dam, the existing design could not be directly applied to construction implementation. This was due to limitations in planning scale related to space, cost, and time, necessitating a design review of several design parameters throughout the dam construction. The data required for this method includes design and embankment construction data, covering laboratory test results of material samples, dam geometry data, and quarry and borrow area locations. This review utilizes these three data sets to generate a comparison between the design from the planning stage and the actual conditions in the field, encompassing location characteristics, physical and mechanical properties of materials, and available embankment volume.